Hariścandra, arthāt, Sūryavamśī Kośaleśa Mahārāja Hariścandra ke udāra carita kā ādarśa - Ratnākara, Jagannāthadāsa, 1866-1932 (SAMP early 20th-century Indian books project, 1948)
Poem on Hariścandra, Hindu mythology.